1995
DOI: 10.1111/j.1432-1033.1995.tb20366.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Human Urokinase Receptor Gene and Its Similarity to CD59 and the Ly‐6 Family

Abstract: Urokinase plasminogen activator receptor (uPAR) gene expression has been implicated in many important biological processes including cell invasiveness and migration. The uPAR gene was cloned from a human genomic library by hybridization with a uPAR cDNA. The complete structure of the human uPAR gene, including a 21.23‐kb transcription unit with 204 bp 5′ and 239 bp 3′ flanking sequences, was determined by comparison with the uPAR cDNA sequence. The uPAR gene is composed of seven exons and six introns. The seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
61
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 29 publications
1
61
0
Order By: Relevance
“…Furthermore, the increase in UPAR mRNA levels also correlated linearly with the progression of disease stage. UPAR is a glycosyl-phosphatidylinositol-linked membrane protein lacking transmembrane and cytosolic domains (11,12) that participates in the localization of plasminogen activation to the cell surface. This cell surface activity facilitates cellular movement by proteolytic extracellular matrix degradation for tumor cell invasion, chemotaxis, and cellular adhesion (13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…Furthermore, the increase in UPAR mRNA levels also correlated linearly with the progression of disease stage. UPAR is a glycosyl-phosphatidylinositol-linked membrane protein lacking transmembrane and cytosolic domains (11,12) that participates in the localization of plasminogen activation to the cell surface. This cell surface activity facilitates cellular movement by proteolytic extracellular matrix degradation for tumor cell invasion, chemotaxis, and cellular adhesion (13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…The wild type u-PAR promoter-driven CAT reporter consists of 398 base pairs of upstream sequence of the u-PAR gene (relative to the transcription start site) cloned into the XbaI site of the pCAT-Basic vector (Promega, Madison, Wisconsin) (Wang et al, 1995). The AP-1 mutated (7184) u-PAR promoter-regulated CAT reporter has been described previously (Lengyel et al, 1996).…”
Section: Dna Constructsmentioning
confidence: 99%
“…A 449 nucleotide u-PAR promoter fragment (Wang et al, 1995) stretching from 7398 to +51 (relative to the transcription start site) was cloned into the XbaI site of the pCAT-Basic vector (Promega, Madison, Wisconsin). The CL100 expression vectors, kindly provided by SM Keyse, University of Dundee, UK, encodes an active (CL100a pSG5) or inactive (CL100i pSG5) CL100 phosphatase (Alessi et al, 1993;Keyse and Emslie, 1992).…”
Section: Vectors and Antibodiesmentioning
confidence: 99%
“…The 7 exon human u-PAR gene has been located to chromosome 19q13 (Vagnarelli et al, 1992;Casey et al, 1994) and is transcribed into a 1.4 kb mRNA or an alternatively spliced variant which lacks the carboxy-terminal membrane attachment peptide sequence (Roldan et al, 1990;Pyke et al, 1993). Although up to 1500 base pairs of upstream sequence, which includes putative binding sites for PEA3, AP-2, Sp1 and NF-kB but no potential TATA or CAAT boxes, has been determined, this and other laboratories have shown that a proximal region of the promoter containing 398 base pairs of sequence is su cient for the constitutively elevated and the phorbol ester-inducible expression of the gene in diverse cell types (Soravia et al, 1995;Wang et al, 1995;Lengyel et al, 1996).…”
Section: Introductionmentioning
confidence: 96%